Cornifronus gen. nov., a new dark sac spider genus from China (Araneae: Trachelidae) - Jin, Chi; Li, Liangtao; Zhang, Feng (Zootaxa, 2024)
A new genus of the spider family Trachelidae L. Koch, 1872, Cornifronus gen. nov. from China is described, as well as one new species, C. simplex sp. nov. (♂♀), known only from Hainan and Yunnan Province.